Relation between serum levels of advanced glycation end products and omentin in type 2 diabetes mellitus subjects - Vifriana; Kurniawan, Liong Boy; Nurahmi; Alfian Zainuddin, Andi; Umar, Husaini; Ariyandy, Andi (Gaceta Médica de Caracas, 2024)
Diabetes mellitus Type 2 (DMT2) is a chronic disease characterized by high levels of sugar in the blood (hyperglycemia) that can cause serious, potentially life-threatening complications. Chronic hyperglycemia, combined with oxidative stress, is known to enhance the formation of advanced glycation end products (AGEs) as a normal consequence of metabolism. Continued elevation of AGEs is known to contribute to the complications of diabetes by raising intracellular oxidative stress. It has been suggested that Omentin is negatively correlated with oxidative stress. Omentin is an adipokine with anti-inflammatory and anti-insulin resistance properties synthesized abundantly in the visceral adipose tissue.